Survival outcomes and prognostic factors of mortality for female breast cancer patients in Malaysia from 2015 to 2019 - Saharudin, Siti Nurhafizah (2025)
Background: Breast cancer remains the leading cancer among women in Malaysia, with survival influenced by sociodemographic and clinical factors. Despite advances in detection and treatment, national level data on survival outcomes and mortality predictors remain limited for evaluating program effectiveness. Objective: This study aimed to estimate survival outcomes and identify prognostic factors of mortality among female breast cancer patients in Malaysia from 2015 to 2019. Methodology: A retrospective cohort study was conducted using data from the Malaysian National Cancer Registry. Data for female patients diagnosed with breast cancer from 2015 to 2019 were followed for five years. Survival was estimated using Kaplan-Meier method, and prognostic factors were assessed with Cox proportional hazards regression. Result: A total of 26,867 eligible cases were analysed. The 5-year survival rate was 57.5% (95% CI: 57.2-57.8) with four prognostic factors were identified. Women aged ≥50 years had a higher mortality risk than younger women (adjusted hazard ratio [aHR]: 1.24; 95% CI: 1.19–1.29; p<0.001). Ethnicity was significant, with Chinese (aHR: 0.78; 95% CI: 0.75–0.81; p<0.001) and Indian (aHR: 0.85; 95% CI: 0.80–0.91; p<0.001) women showing lower risks of mortality than Malays. Stage at diagnosis was the important prognostic factors in this analysis, with mortality risk increasing substantially for stage II (aHR: 1.87; 95%CI: 1.66, 2.10; p<0.001), stage III (aHR: 4.13; 95% CI: 3.69, 4.62); p<0.001), and stage IV (aHR: 11.03; 95% CI: 9.88, 12.32; p<0.001) compared with stage I. Tumor morphology was also associated with variation in survival outcomes. Conclusion: This nationwide study provides updated evidence on breast cancer survival in Malaysia and its key prognostic factors. Strengthening early detection, equitable access to treatment, and registry-clinical data integration are essential to enhance outcomes.